Peptibody Based on FGFR1-Binding Peptides From the FGF4 Sequence as a Cancer-Targeting Agent - Jendryczko, Karolina; Rzeszotko, Jakub; Krzyscik, Mateusz Adam; Szymczyk, Jakub; Otlewski, Jacek; Szlachcic, Anna (Frontiers in Pharmacology, 2021)
Targeted therapies are a promising alternative to conventional chemotherapy, with an increasing number of therapeutics targeting specific molecular aberrancies in cancer cells. One of the emerging targets for directed cancer treatment are fibroblast growth factor receptors (FGFR) – known to be involved in the pathogenesis and progression of multiple cancer types, especially in lung, bladder and breast cancers. Here, we are demonstrating the development of the FGFR1-targeting agent based on interactome screening approach, based on the isolation of binding regions from ligands interacting with receptor. Parallel analysis by FGFR1 pull-down of chymotryptic peptides coupled with MS analysis, and PepSpot analysis yielded equivalent peptide sequences from FGF4, one of the FGFR1 ligands. Three sequences served as a basis for peptibody (Fc-fusion) generation, to overcome clinical limitations of peptidic agents, and two of them showed favorable FGFR1-binding in vitro and FGFR1-dependent internalization into cells. To validate if developed FGFR1-targeting peptibodies can be used for drug delivery, similarly to the well-established concept of antibody-drug conjugates (ADC), peptibodyF4_1 was successfully conjugated with monomethylauristatin E (MMAE), and has shown significant and specific toxicity towards FGFR1-expressing lung cancer cell lines, with nanomolar EC50 values. Essentially, the development of new effective FGFR1-binders that comprise naturally occurring FGFR-recognition peptides and Fc region ensuring high plasma stability and long bloodstream circulation is an interesting strategy expanding targeted anticancer agents portfolio. Furthermore, identifying peptides effectively binding the receptor from sequences of its ligands is not limited to FGFRs and is an approach versatile enough to be a basis for a new peptide/peptibodies development strategy.